KOMPETENSI PEDAGOGIK GURU DALAM PEMBELAJARAN PAI SESUAI KURIKULUM 2013 PADA KEGIATAN PLPG DI FITK UIN SUNAN KALIJAGA YOGYAKARTA - Nur Munajat (Jurnal Pendidikan Agama Islam, 2016)
This study aims at describing teachers’ pedagogical competence in teaching Islamic Studies in accordancewith the 2013 curriculum on the PLPG activities of FITK of UIN Sunan Kalijaga Yogyakarta.Determination of the research subject used purposive sampling technique. The data collection wasdone by the methods of documentation, observation and interviews. While data analysis used the stagesof data reduction, data display, and data verification. The research results show that: (1). Teachers’achievement of pedagogical competence in teaching in accordance with 2013 curriculum in the PLPGactivities reached the average score of 71 percent, or in the category of fairly good. (2). Factors inhibitingthe mastery of competencies are, among others, the short PLPG duration, lack of adequate training on2013 curriculum by the government, and the unavailability of instructional media of LCD projectorsin schools, and the lack of KKG and MGMP guidance. (3). The necessary solutions are, among others,continuous teaching profession development programs, especially on learning strategies, utilization ofinformation technology, and education of teaching profession (PPG) in occupation.Keywords: Pedagogical Competence, Islamic Studies Teaching, 2013 Curriculum.